(untitled) (Journal of the College of Basic Education, 2022)
This means the research study design banner and how to achieve communicative function in Iraqi newspapers being considered as a means of communication between the designer and the reader who always and start looking for new insatiable desires and inclinations in the field of design journalist.The research has included the first chapter and the research problem, where they found the researcher through the study exploratory absence Position connectivity to send content design for letterhead paper and then placed researcher goals discussed identifying ways design banner and detection function communication has been limited border objectivity on the letterhead Iraqi newspapers then identified researcher some terms mentioned in the title search and reached after its presentation to the operational definition is consistent with the goal of current research. The second chapter included theoretical framework implies beneath the first section including design letterhead Iraqi newspapers. The second section handled the communicative function of letterhead newspapers.This has resulted in the theoretical framework for effects were utilized in the development of the analysis of the samples form ..... The third chapter represents the analysis of the seven samples that have been selected I mean according to what suits and placed search.